2013
DOI: 10.5713/ajas.2012.12580
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Electron-beam Irradiation and Leek Extract on the Quality of Pork Jerky during Ambient Storage

Abstract: To investigate the synergistic effect(s) of electron-beam (EB) irradiation and leek (Allium tuberosum Rottler) extract on the quality of pork jerky during ambient storage, we irradiated prepared pork jerky samples (control and samples with 0.5% and 1.0% leek extract) with EB technology at doses of 0, 1, 2, and 4 kGy, stored them for 2 months at 25°C, and analyzed them. Water activity was 0.73 to 0.77 in non-irradiated samples, and no significant difference in the water activity was observed between the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
6
15
0
Order By: Relevance
“…Higher L * value (61.67 ± 1.15) was found in smoked duck meat treated with 1.5 kGy at 40 d of storage, while the minimum L * value (60.22 ± 0.82) was found in the untreated (0 kGy) control on 0 d. The results showed that except for the a * value, Hunter color values increased as the dose of irradiation increased on 0 d; storage had no effect on a * and b * values. Our results agree with those of Kim and others (), who reported that the L * and b * values of e‐beam irradiated pork jerky were increased as the dose of e‐beam increased from 0 to 4 kGy. Nam and others () reported that turkey breast meat became pink after irradiation because of the formation of a CO‐Mb complex.…”
Section: Resultssupporting
confidence: 93%
“…Higher L * value (61.67 ± 1.15) was found in smoked duck meat treated with 1.5 kGy at 40 d of storage, while the minimum L * value (60.22 ± 0.82) was found in the untreated (0 kGy) control on 0 d. The results showed that except for the a * value, Hunter color values increased as the dose of irradiation increased on 0 d; storage had no effect on a * and b * values. Our results agree with those of Kim and others (), who reported that the L * and b * values of e‐beam irradiated pork jerky were increased as the dose of e‐beam increased from 0 to 4 kGy. Nam and others () reported that turkey breast meat became pink after irradiation because of the formation of a CO‐Mb complex.…”
Section: Resultssupporting
confidence: 93%
“…The citrus peel and onion peel extracts were obtained by treating respective peels with 70% ethyl alcohol for 72 h at room temperature, followed by evaporating the solvent (Kim et al, 2013). Thereafter, the extracts were lyophylized using a freeze drier (Il Shin Lab.…”
Section: Sample Preparationmentioning
confidence: 99%
“…During lipid oxidation, although lipid hydroperoxides are the primary products, they eventually convert to peroxides (Kim et al 2013a). Therefore, to study the extent of oxidation in meat, it seemed reasonable to determine the concentration of peroxides in the pork samples.…”
Section: Levels Of Vbn Pov and Tbarsmentioning
confidence: 99%